1973
DOI: 10.1080/14640747308400323
|View full text |Cite
|
Sign up to set email alerts
|

An Apparent New Instance of Stimulus Intensity Dynamism during Discrimination of Duration of Repeating Auditory Stimuli

Abstract: South Parks Road, Oxford 0x1 3PSRats were trained on a VI/EXT discrimination using barpressing in a Skinner box for food reinforcement. The discriminanda consisted of different proportions of noise to silence within a fixed 3-s noise-plus-silence repeating cycle. These stimuli were easily discriminated by human subjects, but the rats formed the discrimination only poorly and after considerable training. Analysis of response rates during noise and silence separately within the 3-s noise-plus-silence cycle showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…There was no lesion effect when the tone signaled the positive trials, though there was an effect when the tone signaled negative trials (Freeman, Kramarcy & Lee 1973). The tendency to respond on negative trials when a tone is sounding has also been observed in normal rats and is taken to demonstrate stimulus-intensity dynamism rather than any influence on learning or memory (Macmillan, Gray & Ison 1973). Hence the sensory nature of the cue is a critical determinant of the lesion effect.…”
Section: Task Classificationmentioning
confidence: 95%
“…There was no lesion effect when the tone signaled the positive trials, though there was an effect when the tone signaled negative trials (Freeman, Kramarcy & Lee 1973). The tendency to respond on negative trials when a tone is sounding has also been observed in normal rats and is taken to demonstrate stimulus-intensity dynamism rather than any influence on learning or memory (Macmillan, Gray & Ison 1973). Hence the sensory nature of the cue is a critical determinant of the lesion effect.…”
Section: Task Classificationmentioning
confidence: 95%
“…Interestinlgy, when we compared behavioral performance for proficient mice between sessions rewarded for high vs. low concentrations we noticed that the number of FAs increased when the rewarded stimulus was the low odorant group (Figure 7A). The increased FAs could be due to the effect of stimulus strength on behavioral responsiveness (Macmillan et al, 1973;Sun and Landy, 2016). The increased FA in the low concentration condition increased the variance of percent correct performance revealing a substantial correlation between decoding the reinforced stimulus from tPRP and behavioral performance for the proficient animal (Figures 7F,G).…”
Section: Discussionmentioning
confidence: 94%
“…The optimal point is in the approximate range of 60-75 dB (SPL), and further increases in ambient noise thereafter have a deleterious effect. The increasing early part of the function may reflect an arousal consequence of the noise, a consequence which may be noted similarly in a variety of reflexive and nomeflexive behaviors (for example, Ison & Leonard, 1971;MacMillan, Gray, & Ison, 1973;Sheard, Astrachan, & Davis, 1975). The reason for the terminal downturn is not unambiguous but it may be produced by the increasingly unfavorable signal/noise ratio as the background level noise approaches the intensity of the eliciting stimulus signal (Ison & Hammond, 1971).…”
mentioning
confidence: 99%